Analisis Pengaruh Persepsi Kualitas Pelayanan Terhadap Kepuasan Masyarakat pada Badan Pelayanan Perijinan Terpadu Kota Tegal - Liris Kristina (Universitas Peradaban, 2015)
Public services can be defined as service activities are carried out as the basic need fulfilment accordance fundamental right of every citizen and resident on the goods, service and admnistration services which is provided by service organizer related to the interest of public. This study analyzed the effect of service quality perception toward the community satisfaction in Tegal integrated licency services agency (Badan Pelayanan Perijinan Terpadu Kota Tegal) the writer uses questionnaire of 100 people who took care of licensing and multiple linear regression analysis to the effect between the dependent and independent variables. The result the multiple linear regression analysis and equation regression are Y = 0,151 + 0,189X1 + 0,554 X2 + 0,255 X3 + 0,355X4 + 0,469X5 obtained the coefficient of determination (R Square) = 0,842; Durbin Watson (DW) = 2,179; Tolerance and VIF tes value indicate non multicolinearity, scatterplot graph form that spreads above and below number 0 not formed a definite pattern which indicate non heteroscedasticity. Besides F counting value is more than F table it can be concluded that physical evidence, reliability, responsiveness, assurance, and emphaty have significant effect toward people satisfaction of Tegal integrated licency service agency (Badan Pelayanan Perijinan Terpadu Kota Tegal) improvement toward public service.